Firms´ Informality and Networks in Mexico: A Cross Section Analysis - Cotler, Pablo (2018)
Many governments have lower taxes and simplifiy regulatory requirements as a way to reduce the number of small firms operating in an informal manner. However, the impact has been slim. We postulate that the informal networks in which many of these firms operate can explain this result. To support our claim, we first build a theoretical model to describe why informality not only depends on the regulatory costs. Next, we use the 2012 Mexican National Survey of Microenterprises to show that its financial networks, and how formal its commercial partners are—once potential endogeneity is acounted for—features that are correlated with how firms are managed. While those that wish to avoid the administrative and/or financial burden of regulation may well be induced to become more formal if regulatory costs are reduced, for many others it is not necessarily regulatory costs, but rather, the benefits to be reaped by becoming formal.